A study of the medical records management practices in selected general hospitals in Manila and Quezon City - Sy, Anthony Jordan L. (School of Library and Information Studies, University of the Philippines Diliman, 2004)
The study focused on the current medical records management practices and procedures of three of the largest general hospitals in Metro Manila in comparison to the medical records practices and procedures of a general hospital in amore developed country, the United States.